Social inhibition as a mediator of neuroticism and depression in the elderly - Wongpakaran Nahathai; Wongpakaran Tinakon; van Reekum Robert (BMC Geriatrics, 2012)
Abstract Background A number of factors, such as demographics, cognitive function, personality and interpersonal relationship) play a role in late-life depression. This study investigates the influence of social inhibition on the inverse emotional stability (neuroticism) and depressive symptoms found in elderly Thai people. Methods In total, 123 elderly Thais aged 60 years of age or older were tested using the 64-item Inventory of Interpersonal Problems, Symptom Checklist-90, and the 16 Personality Factors Questionnaire. Hierarchical regression and path analyses were performed in order to identify the relationships among these variables. Results The age of the participants ranged from 60 to 93 years old (mean = 71.7; SD = 6.2), and out of the group, 51.2% were male, 56.1% were married and 61.8% were on a low income. The average number of years spent in education among the participants was 7.6 (SD = 5.1). The variables found to be significantly associated with depression were age, intellect, social inhibition and possession of inverse emotional stability (neuroticism). Low levels of emotional stability were most strongly associated with depressive symptoms (standardized regression coefficients −0.29), but this effect was found to be reduced (mediated, to −0.26) by social inhibition. In total, 30% of the total variance could be explained by this model, and there was an excellent statistical fit. Conclusions The variables found to be significantly associated with depression were a younger age, as well as lower levels of intellectual skill, social inhibition and inversed emotional stability (neuroticism). It was found that a lack of emotional stability is, along with a younger age, the strongest predictor of depressive symptoms, but can be mediated by social inhibition.